2017
DOI: 10.1186/s12888-017-1297-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Transdiagnostic internet-based treatment for emotional disorders with a specific component to address positive affect: Study protocol for a randomized controlled trial

Abstract: BackgroundEmotional disorders (ED) are among the most prevalent mental disorders. However, less than 50% of people suffering from ED receive the appropriate treatment. This situation has led to the development of new intervention proposals based on the transdiagnostic perspective, which tries to address the underlying processes common to ED. Most of these programs focus primarily on down-regulating negative affectivity, rather than increasing strengths and up-regulating positive affectivity. The data suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 106 publications
(128 reference statements)
0
21
0
3
Order By: Relevance
“…Two subsamples were used for the analysis of sensitivity to change. Subsample 1 consisted of 24 patients who completed an Internet-based treatment for depression [ 52 ], and subsample 2 was made up of 68 patients who underwent a transdiagnostic Internet-based treatment for anxiety and depressive disorders [ 53 , 54 ]. To examine potential floor and ceiling effects for the OASIS scores, the frequency and percentage of minimum (0) and maximum (20) scores was tabulated for subsamples 1 and 2 on the pretest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two subsamples were used for the analysis of sensitivity to change. Subsample 1 consisted of 24 patients who completed an Internet-based treatment for depression [ 52 ], and subsample 2 was made up of 68 patients who underwent a transdiagnostic Internet-based treatment for anxiety and depressive disorders [ 53 , 54 ]. To examine potential floor and ceiling effects for the OASIS scores, the frequency and percentage of minimum (0) and maximum (20) scores was tabulated for subsamples 1 and 2 on the pretest.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the total sample completed the OASIS before and immediately after receiving an Internet-based treatment. Thus, 24 patients received Smiling is Fun [ 52 ] (hereinafter subsample 1 ), and 68 patients received Emotion Regulation [ 53 , 54 ] (hereinafter subsample 2 ). Smiling is Fun is an 8-module Internet-based treatment for depression that includes components of evidence-based treatments.…”
Section: Methodsmentioning
confidence: 99%
“…The other RCT seeks to study the differential efficacy of a transdiagnostic IBT that includes a treatment component to enhance positive affectivity in a community sample. In this protocol, the contents are organized in 16 modules ( Díaz-García et al, 2017 ). These two studies have three important characteristics in common: 1) Both treatments target ED, namely, major depressive disorder, dysthymic disorder, social anxiety disorder, generalized anxiety disorder, panic disorder, agoraphobia, obsessive-compulsive disorder, and not otherwise specified mood and anxiety disorders; 2) Both treatments are based on the transdiagnostic approach to the treatment of ED ( Barlow et al, 2004 ) for which several studies have shown its the efficacy and effectiveness in improving symptomatology, functionality, quality of life, and emotion regulation skills of patients with emotional disorders in both naturalistic and randomized controlled trials (RCTs) ( Dear et al, 2011 , Farchione et al, 2012 , Johnston et al, 2011 , Titov et al, 2013 ); and 3) Both treatment protocols are web-based, self-administered treatments with minimum contact/support from a therapist that consists in a weekly phone call lasting 5 to 10 min to each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Sample 1 included participants with a diagnosis of anxiety and/or depressive disorder that received a transdiagnostic Internet-based protocol for emotional disorders; sample 2 included participants with a diagnosis of adjustment disorder that participated in an Internet-based protocol for the treatment of these disorders; and sample 3 included participants with a diagnosis of depression that received a brief online depression protocol. A full description of the treatments can be found elsewhere [35][36][37]. All the participants were assessed with a structured diagnostic interview.…”
Section: Participants and Proceduresmentioning
confidence: 99%